2020
DOI: 10.4081/jphr.2020.1792
|View full text |Cite
|
Sign up to set email alerts
|

Medication Understanding and Health Literacy among Patients with Multiple Chronic Conditions: A Study Conducted in Bangladesh

Abstract: Objectives: Medication understanding is critical for patients who suffer from multiple chronic conditions in order to reduce medication error and is often associated with poor health outcomesand low adherence. This study aims to identify the gap of medication knowledge among multiple chronic condition patients in Bangladesh, in order to aid physicians and other healthcare providers in improving health literacy.Methods: Individual interviews of a convenience sample of multiple chronic condition patients in Bang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…With respect to the effects of age on OTC drug label misunderstanding, this study demonstrated that misunderstanding was not influenced by age, but a previous study has indicated that misconceptions and confusion about using OTC analgesics are common among adolescents aged 14–20 years old [ 33 ]. Moreover, older adults appear to have more knowledge of and experience with using OTC drugs, but are prone to adverse drug reactions due to existing chronic health conditions and poly-pharmacy [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…With respect to the effects of age on OTC drug label misunderstanding, this study demonstrated that misunderstanding was not influenced by age, but a previous study has indicated that misconceptions and confusion about using OTC analgesics are common among adolescents aged 14–20 years old [ 33 ]. Moreover, older adults appear to have more knowledge of and experience with using OTC drugs, but are prone to adverse drug reactions due to existing chronic health conditions and poly-pharmacy [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study by Frank J. et al, also showed similar results with participants being more knowledgeable on administration schedule and dose but having less knowledge on indication of the medicine and adverse effects [ 9 ]. In a study done in Bangladesh, only 12% of participants identified the medicines by their generic names but the dosage regimen and the administration details was known by 90% of participants [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with polypharmacy were 93% less likely to report a drug's purpose correctly. Negative health outcomes, particularly in older adults, have been associated with polypharmacy 14 , and knowledge of the purpose of all medications was inversely associated with this phenomenon 15 . Polypharmacy was also linked to non-adherence, and this association may be explained by the fact that patients who are unaware of a drug's purpose may be less likely to use it.…”
Section: Discussionmentioning
confidence: 99%